2015
DOI: 10.1177/1470595815594636
|View full text |Cite
|
Sign up to set email alerts
|

Trigunas in organizations

Abstract: The present study tests an alternative and indigenous theory of personality and explores its links with various aspects of organizational behavior. According to the Indian philosophy, trigunas (three trait-like components), namely, sattva, rajas, and tamas, are present in everyone, but it is the relative predominance of one of the three gunas that determines the personality of an individual. Sattva guna is reflected in equanimity, serenity, and poise. Rajas is expressed in high action orientation, ambition, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Apart from the gratitude research, the contribution of the present study could be seen in the background of the call for context-specific indigenous research by propounders and followers indigenous school of thought. Any scientific investigation is incomplete without explanations from different cultural worldviews (Anuradha & Kumar, 2015 ). Indigenous research provides alternate ways of knowing (Jack & Westwood, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the gratitude research, the contribution of the present study could be seen in the background of the call for context-specific indigenous research by propounders and followers indigenous school of thought. Any scientific investigation is incomplete without explanations from different cultural worldviews (Anuradha & Kumar, 2015 ). Indigenous research provides alternate ways of knowing (Jack & Westwood, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of study 3 support their proposition of sattva gun _ a impacting PsyCap. Similarly, Anuradha and Kumar (2015) predicted that Karma Yoga could impact positive organizational outcomes. Study 3 supported this prediction by demonstrating Karma Yoga's impact on positive psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-cultural management scholarship can be enriched only when integrated with explanations from different cultural worldviews (Anuradhaand Kumar, 2015). For that purpose, high-quality, context-specific indigenous research needs to be facilitated (Tsui, 2007).…”
Section: Implications For Cross-cultural Managementmentioning
confidence: 99%
“…Hence, it is likely that they would also have higher performance than others. In a study of Indian banks, Anuradha and Kumar (2015) found that managers who were high on sattva also had higher job performance. Hence, we propose the following hypothesis.…”
Section: Scale Validationmentioning
confidence: 99%